One-piece Ti 2 Additive manufacturing method of AlNb / TiAl gradient structure
Through laser directional energy deposition technology and heat treatment process, the integrated molding of Ti2AlNb/TiAl gradient structure is realized, which solves the problems of long preparation cycle, complex process and low efficiency in the existing technology, and realizes the rapid and economical production of aeroengine integral blisk. , Defect-free gradient structure preparation.
Patent Information
- Application Number
- CN202410541286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The prior art cannot meet the needs of preparing dual alloy gradient structures, and cannot achieve different parts and meet the requirements of different service performance and service temperatures. It also has a long preparation cycle, complex process, low efficiency, high cost, and complex gradient structure preparation.
Laser directed energy deposition technology (L-DED) is used to deposit Ti2AlNb and TiAl alloy powder layer by layer through coaxial four-way powder feeding. Combined with the heat treatment process, the integrated molding of the Ti2AlNb/TiAl gradient structure is achieved.
The rapid integrated molding of the overall leaves of the aviation engine, reducing the preparation cycle and cost, simplifying the process, improving efficiency, and ensuring the good metallurgical binding and no defective molding of the gradient structure.
Smart Images

Figure CN118455548B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of integrally formed aero-engine blisks, and in particular to an additive manufacturing method for integrally formed Ti2AlNb / TiAl gradient structures. Background Art
[0002] The selection of aviation materials has extremely high requirements. Not only must they have excellent comprehensive mechanical properties, but they must also be resistant to high temperatures, low temperatures, and corrosion. TiAl alloy, as a lightweight, high-temperature resistant material, can be used at temperatures of 650-850°C. It has low density, high specific strength, high thermal strength, excellent high-temperature mechanical properties, and corrosion resistance. Therefore, it can be used as a potential first choice material for high-pressure compressors and low-pressure turbine blades of aircraft engines, giving it broad application prospects in the aerospace field. Similarly, Ti2AlNb has the advantages of low density, high elastic modulus, high high-temperature strength, high fracture toughness, high creep resistance, low thermal expansion coefficient, non-magneticity, and good flame retardancy, and also has broad application prospects in the aerospace field.
[0003] When the aircraft engine blisk is in service, the temperature and load-bearing conditions of the blades and the disk body are very different. Even for the same component, the temperature and mechanical properties required of different parts are also different.
[0004] Specifically, the operating temperature of its blades is very high, and they are mainly subjected to centrifugal tensile stress; while the service temperature of its disk body is relatively low, but it will be subjected to greater multi-axis cyclic stress, and the temperature gradient and stress gradient from the center to the edge of the disk cannot be ignored.
[0005] In order to solve the different service conditions of the integral blade disk and significantly improve the service capacity of the blade disk, the existing technology provides a variety of solutions, but these solutions have more or less technical defects.
[0006] Among them, Chinese patent CN112981156A discloses a Ti2AlNb particle plasticized TiAl-based composite material and a preparation method. The method uses a laser direct deposition process and the grain refinement and plasticization of Ti2AlNb particles to make the prepared TiAl-based composite material have excellent room temperature and high temperature mechanical properties. The room temperature tensile strength is measured to be above 530 MPa and the elongation is above 2.5%. Although the use of particle plasticization and laser deposition technology can promote the development and application of TiAl-based materials in engine parts, it is not suitable for the technical requirements of different parts that are subjected to different temperatures and have different mechanical properties.
[0007] Chinese patent CN116079071A discloses an electron beam selective melting additive manufacturing method and equipment for TiAl-Ti2AlNb gradient materials. The method shows that the preparation of TiAl-Ti2AlNb gradient materials is achieved by the electron beam selective melting (EBSM) additive manufacturing method; however, based on the molding principle of EBSM printing, when slicing the three-dimensional model of the integral blade disk, because the central blade disk is Ti2AlNb and the outer blades are TiAl materials, the printing process needs to spread powder layer by layer, and the existing technical defects are: even if the method proposes a system based on improving the existing EBSM equipment and increasing powder recovery, firstly, it does not clearly express how to accurately control the precise separation of different powders on the powder bed when recycling the two powders, and there will inevitably be mixing of the two powders during powder spreading and recovery, resulting in the inability of the molded structure to achieve a precise gradient; secondly, if printing large components, EBSM needs to switch and recover powder for each layer printed, and there are fundamental problems such as long powder spreading time, easy mixing of the two powders, and inability to connect the two material components of the molded parts.
[0008] Chinese patent CN117737619A discloses a directional heat treatment method for a multi-level gradient structure of a Ti2AlNb alloy. This method achieves gradient control of the grain size of the B2 phase in different regions by controlling the temperature variable through temperature-controlled directional induction heating, and develops a gradient heterogeneous structure of the Ti2AlNb alloy based on the B2 grain size. It is obvious that the multi-level gradient structure of the TiAl alloy is achieved by temperature control, which greatly increases the preparation cycle and processing difficulty. Summary of the invention
[0009] The technical problem to be solved by the present invention is that the existing technology cannot meet the requirements of preparing dual alloy gradient structures, and cannot achieve different parts, meet the requirements of different service performance and service temperature. The preparation of gradient materials proposed in the existing technology or invention requires equipment improvement, and has a long preparation cycle, complex process, low efficiency, high cost, and complex preparation of gradient structures, and cannot achieve the one-piece molding preparation of the current aircraft engine integral blade (disc integrated component).
[0010] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:
[0011] An additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure, the additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure comprises the following steps:
[0012] S1. Powder drying:
[0013] Pre-drying the Ti2AlNb and TiAl alloy powders to obtain dried Ti2AlNb and TiAl alloy powders;
[0014] S2. Substrate pretreatment:
[0015] Pre-treating the substrate on which the Ti2AlNb and TiAl alloy powders dried by S1 are to be placed to obtain a pre-treated substrate with a clean surface;
[0016] S3. Equipment inspection:
[0017] The equipment for additive manufacturing of Ti2AlNb and TiAl alloy powders dried on the pre-treated substrate with S2 surface cleaning was inspected to confirm that the equipment meets the technical requirements of additive manufacturing and obtain the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure before preparation;
[0018] S4, Argon protection:
[0019] The argon environment box in the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure before S3 preparation is filled with high-purity argon protective gas, and the oxygen content and water content in the environment box are regulated to obtain the prepared equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure;
[0020] S5, substrate preheating:
[0021] Preheating the cleaned pretreated substrate on the inner surface of the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure prepared by S4, so that the temperature of the substrate is increased to reduce the temperature difference in the forming chamber, and obtain the preheated substrate;
[0022] S6, coaxial powder feeding:
[0023] The coaxial four-way powder feeding method is selected to transport the Ti2AlNb and TiAl alloy powders dried in S1 to the preheated substrate in S5;
[0024] S7, parameter setting:
[0025] During the laser directed energy deposition process, the laser beam reciprocates relative to the substrate. After locating the origin on the hot substrate S6 containing powder, some process parameters of the laser directed energy deposition are set according to the product size of the prepared one-piece Ti2AlNb / TiAl gradient structure, and other process parameters of the laser directed energy deposition are set according to the thickness and width of a single layer, and finally the set process parameters are obtained.
[0026] S8, Laser path selection:
[0027] According to the required performance of the prepared integrally formed Ti2AlNb / TiAl gradient structure product, a suitable laser path is selected to perform laser directed energy deposition, and a selected laser path is obtained;
[0028] S9, Gradient deposition powder path switching:
[0029] The dried Ti2AlNb powder is transported to the preheated substrate through the S6 coaxial four-way powder feeding method, and the Ti2AlNb layer is deposited according to the process parameters set by S7 and the laser path selected by S8. After a certain height is deposited, the powder path is directly switched to deposit the TiAl layer on the deposited Ti2AlNb layer to obtain an integrally formed dual alloy gradient material;
[0030] S10, heat treatment process:
[0031] The S9 integrally formed dual alloy gradient material is subjected to annealing heat treatment to obtain an integrally formed Ti2AlNb / TiAl gradient structure product.
[0032] Optionally, the Ti2AlNb alloy powder in S1 is a spherical powder with a powder particle size of 45-150μm; the TiAl alloy powder is a spherical powder, and its components include Ti-48Al-2Cr-2Nb and Ti-45Al-8Nb, and the powder particle size is 45-150μm; the drying treatment is carried out in a drying oven at 80-120℃ for 2-4h, and the water content of the dried Ti2AlNb alloy powder is not higher than 0.1%, and the water content of the TiAl alloy powder is not higher than 0.1%.
[0033] Optionally, the pretreatment in S2 is to manually polish the substrate in the same direction with 80-120 grit sandpaper before starting deposition, and then use a laser cleaning machine to remove oil and oxide layer on the surface of the substrate, and the roughness of the substrate surface is 200-50 μm.
[0034] Optionally, the composition of the substrate in S2 is any one of TC4 alloy, TC11 alloy, and TA15 alloy.
[0035] Optionally, the equipment in S3 mainly includes a laser, a forming control system, a powder feeding system and an oxygen content detection system, and also includes auxiliary units such as an industrial robot, a water cooler, an air compressor, and an argon environment chamber.
[0036] Optionally, the purpose of filling S4 with high-purity argon protective gas is to make the purge time of the large environmental box 3-4h, and the purge time of the small environmental box 0.25-0.5h; the powder carrier gas flow rate is 0.8-1.5L / min, the powder feeding speed is 0.3-1r / min, the central protective gas flow rate is 15-45L / min, and the oxygen content in the environmental chamber is regulated to be lower than 20PPm, and the water content is lower than 0.01PPm.
[0037] Optionally, in S4, the oxygen content in the environmental chamber is regulated to be lower than 20 PPm, and an oxygen content detector is required to dynamically measure the oxygen concentration in the forming chamber.
[0038] Optionally, the holding temperature of the preheating treatment in S5 is 300-500°C, the holding time is 5-10 minutes, and the temperature difference in the molding chamber is reduced to within the range of 100-200°C.
[0039] Optionally, the size of the substrate targeted by the preheating treatment in S5 is 150 mm×150 mm×20 mm.
[0040] Optionally, the preheating treatment in S5 is to deposit a single thin layer on the surface of the TC4 substrate using Ti2AlNb powder according to certain process parameters, so that the substrate temperature is increased to reduce the temperature difference in the molding chamber, thereby avoiding stress release caused by sudden temperature rise during printing, resulting in cracks in the single wall.
[0041] Optionally, in the coaxial four-way powder feeding method in S6, the dried Ti2AlNb and TiAl alloy powders during deposition are not fed into the molten pool from four directions at the same time, and the powder feeding carrier gas is argon.
[0042] Optionally, some process parameters of laser directed energy deposition in S7 include number of cycle layers, laser power, scanning speed, lifting speed, powder feeding rate, carrier gas flow rate, and other process parameters of laser directed energy deposition include lifting height and overlap rate.
[0043] Optionally, when S7 involves multiple paths on the same layer, the radial overlap rate between adjacent single paths is 40-60%.
[0044] Optionally, the laser power of the laser directed energy deposition in S7 is 800-1500 W and the laser scanning speed is 6-10 mm / s.
[0045] Optionally, the laser path selected in S8 is a gradient single wall path or a gradient block path, wherein:
[0046] The scanning path in the gradient single-pass wall path is a single-pass reciprocating cycle. The laser head moves from the origin to the positive direction of the Y axis. The laser scanning speed is 6-10mm / s. The light is emitted and powder is delivered at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a lifting speed of 1.5-2mm / s, and the lifting ΔZ is 0.5-0.7mm. No powder is emitted during the lifting. Subsequently, the laser head moves along the negative direction of the Y axis, and the light is emitted and powder is delivered at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a lifting speed of 1.5-2mm / s, and the lifting ΔZ is 0.5-0.7mm.
[0047] When it is lifted, no powder is discharged. This is a cycle. When the set number of layers is completed, printing is finished.
[0048] In order to increase the heat input between passes and promote better fusion of gradient materials in the gradient block path, a short-side multi-pass overlapping path is used to prepare block gradient materials, and the overlap rate between laser paths is 50%; the laser head moves from the origin to the positive direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and powder is delivered at the same time. When the set length is reached, the laser head moves along the positive direction of the Y-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and powder is delivered at the same time, and the overlap rate is 50%. When the set length is reached, the laser head moves along the negative direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and powder is delivered at the same time. When the set length is reached, the laser head moves along the positive direction of the Y-axis, and the overlap rate is 50%, which is a cycle; after the Y-axis direction meets the length requirement, the laser head is lifted upward along the Z-axis, with a lift of ΔZ=0.7-1.0mm, and no powder is emitted during the lift. The lifting speed is 6-8mm / s, and the path of the previous layer is repeated until the cycle of the set number of layers is completed and printing is completed.
[0049] Optionally, in S9, how is a certain height obtained?
[0050] Optionally, in S9, in order to avoid the bottom cracking and macroscopic cracking of the deposited gradient material caused by the intrinsic brittleness of TiAl alloy if it is directly deposited on the TC4 substrate, 100% Ti2AlNb powder is printed first. When the number of layers reaches a certain height, the powder is switched and 100% TiAl is continued to be printed to form a direct transition dual alloy gradient material.
[0051] Optionally, the certain height in S9 is set according to the required preparation of an integrally formed Ti2AlNb / TiAl gradient structure product, wherein: when the single wall height is set to 20 mm, the single layer thickness is set to 0.5 mm and the height is raised to 0.5 mm. It takes 40 layers to reach the set height of 20 mm. At this time, the powder path is switched to print the next material to realize the preparation of the gradient material.
[0052] Optionally, the heating rate of the annealing heat treatment in S10 is 10-20° C. / min, the annealing temperature is 600-1000° C., the holding time is 2-6 min, and then the furnace is cooled.
[0053] Optionally, the subsequent cutting of the product with the integrally formed Ti2AlNb / TiAl gradient structure in S10 does not cause cracking on the product surface, and the surface of the obtained gradient product has no macro cracks, which is conducive to subsequent machining and heat treatment.
[0054] Optionally, the product of the integrally formed Ti2AlNb / TiAl gradient structure in S10 can further obtain a dual-alloy direct transition gradient material with excellent performance by using the same or optimizing different printing process parameters, thereby realizing gradient connection of multiple alloys.
[0055] Optionally, the product of the integrally formed Ti2AlNb / TiAl gradient structure in S10 is integrally formed by a dual alloy direct transition method, and the dual alloy gradient transition can be further realized by adding a gradient composition transition layer.
[0056] Optionally, the operating temperature of the blades in the one-piece Ti2AlNb / TiAl gradient structure product in S10 is 650-850°C, and the main centrifugal tensile stress it bears can meet the design requirements; while the service temperature of the disk body is 550-650°C, and the multi-axis cyclic stress it bears depends on the design requirements; and the temperature gradient and stress gradient from the center to the edge of the disk can meet the design requirements.
[0057] Technical principle of the present invention:
[0058] Combined with laser directed energy deposition (L-DED) technology, also known as laser direct manufacturing (LDM) or laser metal deposition (LMD), dual-alloy gradient materials that meet different parts, different service performance and temperature requirements can be directly prepared, which is expected to be promoted in the aerospace field.
[0059] A lightweight and high-strength dual-alloy integral turbine blade disk is prepared through one-piece molding, and the two aviation components of the turbine disk and the turbine blade are combined into one. Ti2AlNb is used in the turbine disk area and TiAl is used in the turbine blade area. The good mechanical properties of TiAl in the high temperature zone (650-850℃) and the good plasticity of Ti2AlNb (550-650℃) in the medium temperature zone are comprehensively utilized. In order to help China's aviation engines develop in the direction of lightweight, high strength and high thrust-to-weight ratio, a technical solution is provided for the rapid industrial application of one-piece Ti2AlNb / TiAl dual-alloy gradient materials (hereinafter referred to as dual-alloy gradient materials).
[0060] In order to solve the different service conditions of the integral blade disk and significantly improve the service capacity of the blade disk, different structures need to be prepared on the blade disk and blades according to their service conditions. It is difficult to effectively prepare gradient structures for the TiAl alloy integral blade disk prepared by conventional methods, and the application of additive manufacturing is just suitable for the preparation of gradient materials. If additive manufacturing can be applied to the preparation of Ti2AlNb / TiAl dual alloy gradient materials (Functionally Gradient Material) according to the performance requirements of the components and the service environment, the preparation cycle of the integral blade disk can be greatly reduced, the preparation cost can be reduced, and the development trend of "lightweight, gradient, and structural and functional integration" of the new generation of aviation and aerospace structures can be adapted. Therefore, it is very necessary to develop an additive manufacturing dual alloy gradient material one-piece molding technology.
[0061] Additive manufacturing is a very promising emerging manufacturing technology. It has been widely used in aerospace and other industrial fields due to its advantages such as high degree of freedom and low preparation cycle. In particular, laser additive manufacturing is a technology that uses laser as an energy source to melt metal powder and scan along a path, and completes the forming of solid parts in a layer-by-layer accumulation manner. Relying on its high heat input and cooling rate, it can obtain fine structures different from conventional preparation methods such as forging and casting. Among them, laser directed energy deposition technology or laser metal melting deposition technology (essentially the same process) can achieve mold-free, rapid, and near-net forming of complex structures. Because it has multiple powder hoppers to store different materials, and the powder can be flexibly switched into different types or proportions according to requirements, it can be used to prepare parts of functional gradient materials. It is the optimal solution for the integrated preparation of dual alloy gradient material components with multiple interface transition zones.
[0062] Traditional manufacturing methods have some limitations and challenges when making gradient materials. For example, methods such as powder metallurgy and centrifugal casting are usually difficult to directly manufacture complex gradient structures. These methods require other processing or welding processes to achieve the final shape, which increases the complexity of the production process and the time-consuming production process. In additive manufacturing technology, powder bed fusion technology or electron beam additive manufacturing technology, due to the use of powder laying method, it is difficult to switch between multiple powders, and it is impossible to prepare dual alloy gradient materials. If dual performance gradient materials need to be prepared, the organization can only be regulated by subsequent segmented heat treatment process, which greatly increases the preparation cycle and processing difficulty. In addition, the existing dual alloy gradient materials are less studied and the preparation process is not perfect. Due to the defects of the preparation process, the plastic deformation is higher than the plastic reserve of the bonding interface, and the internal stress causes obvious macroscopic cracking of the bonding interface, which seriously limits the wide application of dual alloy gradient materials. At present, there is no relevant technology that can achieve a one-piece molding process with good metallurgical bonding of two or more titanium aluminum alloy gradient materials.
[0063] On the basis of the above, the present invention directly obtains a gradient material with good metallurgical bonding and good morphology by regulating the laser directional energy deposition technology of Ti2AlNb / TiAl dual alloy material, realizes the direct transition of Ti2AlNb and TiAl alloys, and finally the Ti2AlNb / TiAl dual alloy formed along the transition direction has good morphology, no obvious defects and a smooth surface.
[0064] Specifically, the present invention uses laser as a heat source to heat the powder until it melts, and the molten pool quickly solidifies to form a deposition layer on the substrate. After determining the process suitable for the two alloy materials, by changing the type and ratio of the alloy powder during the deposition process, the expected designed material composition, organizational structure and performance can be obtained at any position of the part, thereby achieving the integrated preparation of gradient functional materials with excellent comprehensive performance, dual alloy gradient materials with multiple interface transition zones, and the final forming of components with good metallurgical bonding and no defects.
[0065] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0066] The above scheme, the present invention proposes an additive manufacturing method for one-piece forming of Ti2AlNb / TiAl gradient structure, which can realize the one-piece forming preparation of the current aircraft engine integral blade disk (a component with an integrated disk) to overcome the technical defect that the existing EBSM technology cannot realize the rapid one-piece forming of dual alloy materials with gradient structure connection, and does not require equipment improvement, has a short preparation cycle, a simple process, high efficiency, low cost, and simple gradient structure preparation.
[0067] The present invention is based on exploring the optimal process for simultaneously adapting two alloys, reducing the difference in adhesion of dissimilar materials after the molten pool solidifies due to excessive cooling rate, and the interactive fusion of the two powders in the molten pool during deposition, which can achieve uniform diffusion of elements in the molten pool, thereby forming a gradient transition zone with multiple interfaces.
[0068] The invention can reduce the thermal stress in the forming process of the transition interface zone of two materials, and realize the direct gradient transition connection of Ti2AlNb and TiAl dual alloy through direct deposition forming.
[0069] The Ti2AlNb / TiAl dual alloy gradient material prepared by the present invention can gradually change the composition and organization of the material properties in a certain direction by gradually changing the material composition, and can meet the requirements of different positions of a component. Therefore, these gradient materials can be applied to specific fields such as aerospace, automobiles, biomedicine and national defense.
[0070] The laser directed energy deposition technology used in the present invention does not rely on a powder bed and is not limited by space size. Therefore, larger parts can be manufactured and are expected to be promoted and applied in the field of integral blade disks of aero-engines.
[0071] The present invention can effectively realize the gradient connection of Ti2AlNb / TiAl dual alloy materials, and good metallurgical bonding occurs at the interface between the dual alloy gradient regions, and there are no fusion defects such as cracks, so that the performance advantages of Ti2AlNb materials can be exerted at medium and low temperatures, and the performance advantages of TiAl materials can be exerted in high temperature regions. Through further optimization of the process, an integrally formed component can be obtained, which can simultaneously meet the requirements of different service temperature zones and different service performances, and can give full play to the excellent performance of Ti2AlNb and TiAl alloys to a greater extent, work under greater temperature gradient and stress gradient conditions, and meet the dual performance requirements of the integral blade in the field of aero-engines.
[0072] In summary, compared with other traditional methods, the method of the present invention realizes the direct gradient transition connection of Ti2AlNb and TiAl dual alloys through laser directed energy deposition technology, and adjusts the process parameters to adjust the product performance of the prepared Ti2AlNb / TiAl gradient structure to meet different performance requirements; this method is conducive to promoting the development of Chinese aviation engines towards lightweight, high strength and high thrust-to-weight ratio, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0074] Figure 1 The morphology of pre-alloyed powders of an additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure of the present invention is shown in FIG. 1 , wherein: (a) is Ti-48Al-2Cr-2Nb powder, and (b) is Ti-22Al-25Nb powder;
[0075] Figure 2 It is a gradient material transition interface region diagram of an additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure of the present invention, wherein: (a) is an EBSD phase composition diagram, and (b) is a SEM microstructure diagram;
[0076] Figure 3 This is an elemental EDS line scan of a direct transition of a gradient material in an additive manufacturing method for an integrally formed Ti2AlNb / TiAl gradient structure of the present invention;
[0077] Figure 4It is a diagram of other gradient material transition regions of an additive manufacturing method for an integrally formed Ti2AlNb / TiAl gradient structure of the present invention, wherein: (a) is an EBSD phase composition diagram, and (b) is a SEM microstructure diagram;
[0078] Figure 5 The macroscopic structure diagram of a single wall of gradient material in an additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure of the present invention, wherein: (a) is a height diagram of a single wall of gradient material, and (b) is a length diagram of a single wall of gradient material;
[0079] Figure 6 The simplified model schematic diagram and macroscopic morphology of a product prepared by an additive manufacturing method for an integrally formed Ti2AlNb / TiAl gradient structure of the present invention, wherein: (a) is a simplified model schematic diagram of the product, and (b) is a macroscopic morphology diagram of the product;
[0080] Figure 7 Schematic diagram of the three-dimensional model and the two-dimensional slice (laser trajectory) of the turbine disk and blade of the product prepared by the additive manufacturing method of the one-piece Ti2AlNb / TiAl gradient structure of the present invention; wherein: (a) is a schematic diagram of the three-dimensional model of the turbine disk, (b) is a two-dimensional slice diagram of the turbine disk, (c) is a schematic diagram of the three-dimensional model of the blade, and (d) is a schematic diagram of the two-dimensional slice (laser trajectory) of the blade. DETAILED DESCRIPTION
[0081] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0082] An additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to an embodiment of the present invention comprises the following steps:
[0083] S1. Powder drying:
[0084] The Ti2AlNb and TiAl alloy powders are pre-dried to obtain dried Ti2AlNb and TiAl alloy powders; wherein: the Ti2AlNb alloy powder is a spherical powder with a powder particle size of 45-150μm; the TiAl alloy powder is a spherical powder, the components of which include Ti-48Al-2Cr-2Nb and Ti-45Al-8Nb, and the powder particle size is 45-150μm; the drying treatment is carried out in a drying oven at 80-120°C for 2-4h, the water content of the dried Ti2AlNb alloy powder is not higher than 0.1%, and the water content of the TiAl alloy powder is different from 0.1%;
[0085] like Figure 1 FIG. 1 is a morphology diagram of a pre-alloyed spherical powder of a raw material used in one embodiment of the present invention, from which it can be seen that the powder is uniform in size and the surface structure presents a typical dendritic structure.
[0086] S2. Substrate pretreatment:
[0087] The substrate on which the Ti2AlNb and TiAl alloy powders dried by S1 are to be placed is pretreated, which is that before starting deposition, the substrate is manually polished in the same direction with 80-120 mesh sandpaper, and then the oil and oxide layer on the surface of the substrate are removed with a laser cleaning machine. The roughness of the substrate surface is 200-50 μm, and a pretreated substrate with a clean surface is obtained;
[0088] S3. Equipment inspection:
[0089] The equipment for additive manufacturing of Ti2AlNb and TiAl alloy powders dried on a pre-treated substrate with a cleaned S2 surface is inspected to confirm that the equipment meets the technical requirements of additive manufacturing and obtains the equipment for additive manufacturing one-piece forming of Ti2AlNb / TiAl gradient structure before preparation; the equipment mainly includes laser, forming control system, powder feeding system and oxygen content detection system, and also includes auxiliary units such as industrial robots, water coolers, air compressors, and argon environment boxes;
[0090] S4, Argon protection:
[0091] The argon environment box in the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure before S3 preparation is filled with high-purity argon protective gas. The purpose of filling with high-purity argon protective gas is to make the large environment box purge time 3-4h, and the small environment box purge time 0.25-0.5h; the powder carrier gas flow rate is 0.8-1.5L / min, the powder feeding speed is 0.3-1r / min, the central protective gas flow rate is 15-45L / min, and the oxygen content in the environmental chamber is regulated to be lower than 20PPm, and the water content is lower than 0.01PPm, so as to obtain the prepared equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure;
[0092] S5, substrate preheating:
[0093] The cleaned pre-treated substrate on the inner surface of the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure prepared by S4 is preheated, the holding temperature of the preheating treatment is 300-500°C, the holding time is 5-10min, the temperature difference in the forming chamber is reduced to within the range of 100-200°C, and the preheated substrate is obtained; the substrate size for the preheating treatment is 150mm×150mm×20mm;
[0094] S6, coaxial powder feeding:
[0095] The coaxial four-way powder feeding method is selected to transport the Ti2AlNb and TiAl alloy powders dried in S1 to the preheated substrate in S5. The coaxial four-way powder feeding method is that the Ti2AlNb and TiAl alloy powders dried during deposition are simultaneously fed into the molten pool from four directions, and the powder feeding carrier gas is argon.
[0096] S7, parameter setting:
[0097] During the laser directed energy deposition process, the laser beam performs reciprocating motion relative to the substrate. After locating the origin on the S6 hot substrate containing powder, some process parameters of the laser directed energy deposition are set according to the product size of the prepared one-piece Ti2AlNb / TiAl gradient structure, including the number of cycle layers, laser power, scanning speed, lifting speed, powder feeding rate, and carrier gas flow rate. Other process parameters of the laser directed energy deposition are set according to the thickness and width of a single layer, including the lifting height and overlap rate. Finally, the set process parameters are obtained.
[0098] S8, Laser path selection:
[0099] According to the required performance of the prepared integrally formed Ti2AlNb / TiAl gradient structure product, a suitable laser path is selected to perform laser directed energy deposition, and a selected laser path is obtained;
[0100] The selected laser path is a gradient single wall path or a gradient block path, where:
[0101] The scanning path in the gradient single-pass wall path is a single-pass reciprocating cycle. The laser head moves from the origin to the positive direction of the Y axis. The laser scanning speed is 6-10mm / s. The light is emitted and powder is delivered at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a lifting speed of 1.5-2mm / s, and the lifting ΔZ is 0.5-0.7mm. No powder is emitted during the lifting. Subsequently, the laser head moves along the negative direction of the Y axis, and the light is emitted and powder is delivered at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a lifting speed of 1.5-2mm / s, and the lifting ΔZ is 0.5-0.7mm. No powder is emitted during the lifting. This is a cycle until the set number of layers is completed and printing is completed.
[0102] In order to increase the heat input between passes and promote better fusion of gradient materials in the gradient block path, a short-side multi-pass overlap path is used to prepare block gradient materials, and the overlap rate between laser paths is 50%; the laser head moves from the origin to the positive direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted while feeding powder. When the set length is reached, the laser head moves along the positive direction of the Y-axis, the laser scanning speed is 6-10mm / s, and the light is emitted while feeding powder, and the overlap rate is 50%. When the set length is reached, the laser head moves along the negative direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted while feeding powder. When the set length is reached, the laser head moves along the positive direction of the Y-axis, and the overlap rate is 50%, which is a cycle; after the Y-axis direction meets the length requirement, the laser head is lifted upward along the Z-axis, with a lift of ΔZ=0.7-1.0mm, and no powder is emitted during the lift. The lifting speed is 6-8mm / s, and the path of the previous layer is repeated until the cycle of the set number of layers is completed and printing is completed;
[0103] S9, Gradient deposition powder path switching:
[0104] The dried Ti2AlNb powder is transported to the preheated substrate through the S6 coaxial four-way powder feeding method, and the Ti2AlNb layer is deposited according to the process parameters set by S7 and the laser path selected by S8. After a certain height is deposited, the powder path is directly switched to deposit the TiAl layer on the deposited Ti2AlNb layer to obtain an integrally formed dual alloy gradient material; wherein: the certain height is set according to the product of the integrally formed Ti2AlNb / TiAl gradient structure to be prepared, wherein: when the single wall height is set to 20mm, the single layer thickness is set to 0.5mm and the height is raised to 0.5mm. It takes 40 layers to reach the set height of 20mm. At this time, the powder path is switched to print the next material to achieve the preparation of the gradient material;
[0105] S10, heat treatment process:
[0106] The S9 integrally formed dual alloy gradient material is subjected to annealing heat treatment, the heating rate of the annealing heat treatment is 10-20°C / min, the annealing temperature is 600-1000°C, the holding time is 2-6min, and then furnace cooling is performed; a product with an integrally formed Ti2AlNb / TiAl gradient structure is obtained.
[0107] like Figure 2 As shown, it is a gradient material transition interface region diagram of a product with an integrally formed Ti2AlNb / TiAl gradient structure prepared in one embodiment of the present invention, from which it can be seen that the direct transition gradient material has three interface transition zones.
[0108] like Figure 3 As shown, this is an element EDS line scan diagram of the direct transition of the gradient material of a product with an integrally formed Ti2AlNb / TiAl gradient structure prepared in one of the embodiments of the present invention. It can be seen from the diagram that in the direct transition gradient material, the elements Nb and Al in the transition interface region present a large atomic concentration gradient, which is consistent with the large concentration gradient of Al and Nb in the initial TiAl and Ti2AlNb alloys.
[0109] like Figure 4 As shown, it is a diagram of other gradient material transition interface regions of a product with an integrally formed Ti2AlNb / TiAl gradient structure prepared according to one embodiment of the present invention, from which it can be seen that the direct transition gradient material has 5 interface transition zones.
[0110] like Figure 5 As shown, it is a macroscopic structure diagram of a single wall of a gradient material of a product of an integrally formed Ti2AlNb / TiAl gradient structure prepared in one embodiment of the present invention. It can be seen from the diagram that the present invention can be used to prepare a dual alloy gradient structure with no surface cracks, smooth morphology and good metallurgical bonding.
[0111] like Figure 6 As shown, it is a simplified model schematic diagram and macroscopic morphology of a product of an integrally formed Ti2AlNb / TiAl gradient structure prepared in one embodiment of the present invention, from which it can be seen that: Figure (a) is a schematic diagram of the three-dimensional model of the integral blade disk, and Figure (b) is a schematic diagram of the simplified gradient integral blade disk.
[0112] like Figure 7 As shown, it is a schematic diagram of the three-dimensional model and a schematic diagram of the two-dimensional slice (laser trajectory) of the turbine disk and blade of the one-piece Ti2AlNb / TiAl gradient structure product prepared according to one embodiment of the present invention. It can be seen that: Figure (a) is a schematic diagram of the three-dimensional model of the simplified turbine disk, Figure (b) is a schematic diagram of the two-dimensional slice (laser trajectory) of the simplified turbine disk, Figure (c) is a schematic diagram of the three-dimensional model of the simplified blade, and Figure (b) is a schematic diagram of the two-dimensional slice (laser trajectory) of the simplified blade.
[0113] In particular, the composition of the substrate in S2 is any one of TC4 alloy, TC11 alloy, and TA15 alloy.
[0114] In particular, in S4, the oxygen content in the environmental chamber is regulated to be lower than 20PPm, and an oxygen content detector is required to dynamically measure the oxygen concentration in the forming chamber.
[0115] In particular, the preheat treatment in S5 is to deposit a single thin layer on the surface of the TC4 substrate using Ti2AlNb powder according to certain process parameters, so that the substrate temperature is increased to reduce the temperature difference in the molding chamber, thereby avoiding the stress release caused by the sudden temperature rise during the printing process, which leads to cracks in the single wall.
[0116] In particular, when multiple paths on the same layer are involved in S7, the radial overlap between adjacent single paths is 40-60%.
[0117] In particular, the laser power of laser directed energy deposition in S7 is 800-1500W and the laser scanning speed is 6-10mm / s.
[0118] In particular, in S9, in order to avoid the bottom cracking and macroscopic cracking of the deposited gradient material caused by direct deposition on the TC4 substrate due to the intrinsic brittleness of the TiAl alloy, 100% Ti2AlNb powder is printed first. When the number of layers reaches a certain height, the powder is switched and 100% TiAl is continued to be printed to form a direct transition dual alloy gradient material.
[0119] In particular, the subsequent cutting of the product with the integrally formed Ti2AlNb / TiAl gradient structure in S10 does not cause cracking on the product surface, and the obtained gradient product surface has no macro cracks, which is conducive to subsequent machining and heat treatment.
[0120] In particular, the one-piece Ti2AlNb / TiAl gradient structure product in S10 can further obtain dual-alloy direct transition gradient materials with excellent performance by using the same or optimizing different printing process parameters, thereby realizing gradient connection of multiple alloys.
[0121] In particular, the one-piece Ti2AlNb / TiAl gradient structure product in S10 is one-piece formed by direct dual alloy transition, and the dual alloy gradient transition can be further realized by adding a gradient composition transition layer.
[0122] In particular, the operating temperature of the blades in the one-piece Ti2AlNb / TiAl gradient structure product of S10 is 650-850℃, and it mainly withstands centrifugal tensile stress depending on the design requirements; while the service temperature of the disk body is 550-650℃, and it withstands multi-axial cyclic stress depending on the design requirements; and the temperature gradient from the center to the edge of the disk depends on the design requirements, and the stress gradient depends on the design requirements.
[0123] The above scheme, the present invention proposes an additive manufacturing method for one-piece forming of Ti2AlNb / TiAl gradient structure, which can realize the one-piece forming preparation of the current aircraft engine integral blade disk (a component with an integrated disk) to overcome the technical defect that the existing EBSM technology cannot realize the rapid one-piece forming of dual alloy materials with gradient structure connection, and does not require equipment improvement, has a short preparation cycle, a simple process, high efficiency, low cost, and simple gradient structure preparation.
[0124] The present invention is based on exploring the optimal process for simultaneously adapting two alloys, reducing the difference in adhesion of dissimilar materials after the molten pool solidifies due to excessive cooling rate, and the interactive fusion of the two powders in the molten pool during deposition, which can achieve uniform diffusion of elements in the molten pool, thereby forming a gradient transition zone with multiple interfaces.
[0125] The invention can reduce the thermal stress in the forming process of the transition interface zone of two materials, and realize the direct gradient transition connection of Ti2AlNb and TiAl dual alloy through direct deposition forming.
[0126] The Ti2AlNb / TiAl dual alloy gradient material prepared by the present invention can gradually change the composition and organization of the material properties in a certain direction by gradually changing the material composition, and can meet the requirements of different positions of a component. Therefore, these gradient materials can be applied to specific fields such as aerospace, automobiles, biomedicine and national defense.
[0127] The laser directed energy deposition technology used in the present invention does not rely on a powder bed and is not limited by space size. Therefore, larger parts can be manufactured and are expected to be promoted and applied in the field of integral blade disks of aero-engines.
[0128] The present invention can effectively realize the gradient connection of Ti2AlNb / TiAl dual alloy materials, and good metallurgical bonding occurs at the interface between the dual alloy gradient regions, and there are no fusion defects such as cracks, so that the performance advantages of Ti2AlNb materials can be exerted at medium and low temperatures, and the performance advantages of TiAl materials can be exerted in high temperature regions. Through further optimization of the process, an integrally formed component can be obtained, which can simultaneously meet the requirements of different service temperature zones and different service performances, and can give full play to the excellent performance of Ti2AlNb and TiAl alloys to a greater extent, work under greater temperature gradient and stress gradient conditions, and meet the dual performance requirements of the integral blade in the field of aero-engines.
[0129] In summary, compared with other traditional methods, the method of the present invention realizes the direct gradient transition connection of Ti2AlNb and TiAl dual alloys through laser directed energy deposition technology, and adjusts the process parameters to adjust the product performance of the prepared Ti2AlNb / TiAl gradient structure to meet different performance requirements; this method is conducive to promoting the development of Chinese aviation engines towards lightweight, high strength and high thrust-to-weight ratio, and is conducive to large-scale industrial production and promotion.
[0130] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure, characterized in that: The additive manufacturing method of the integrally formed Ti2AlNb / TiAl gradient structure comprises the following steps: S1. Powder drying: Pre-drying the Ti2AlNb and TiAl alloy powders to obtain dried Ti2AlNb and TiAl alloy powders; S2. Substrate pretreatment: Pre-treating the substrate on which the Ti2AlNb and TiAl alloy powders dried by S1 are to be placed to obtain a pre-treated substrate with a clean surface; S3. Equipment inspection: Check the equipment for additive manufacturing of Ti2AlNb and TiAl alloy powders dried on a pre-treated substrate with a cleaned S2 surface to confirm that the equipment meets the technical requirements of additive manufacturing and obtain the equipment for additive manufacturing of an integrated Ti2AlNb / TiAl gradient structure before preparation; S4, Argon protection: The argon environment box in the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure before S3 preparation is filled with high-purity argon protective gas, and the oxygen content and water content in the environment box are regulated to obtain the prepared equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure; S5, substrate preheating: Preheating the cleaned pretreated substrate on the inner surface of the equipment for additive manufacturing integrally formed Ti2AlNb / TiAl gradient structure prepared by S4, so that the temperature of the substrate is increased to reduce the temperature difference in the forming chamber, and obtain the preheated substrate; S6, coaxial powder feeding: Select the coaxial four-way powder feeding method to transport the Ti2AlNb and TiAl alloy powders dried in S1 to the preheated substrate in S5; S7, parameter setting: During the laser directed energy deposition process, the laser beam reciprocates relative to the substrate. After locating the origin on the hot substrate S6 containing powder, some process parameters of the laser directed energy deposition are set according to the product size of the prepared one-piece Ti2AlNb / TiAl gradient structure, and other process parameters of the laser directed energy deposition are set according to the thickness and width of a single layer, and finally the set process parameters are obtained. S8, Laser path selection: According to the required performance of the prepared integrally formed Ti2AlNb / TiAl gradient structure product, a suitable laser path is selected to perform laser directed energy deposition, and a selected laser path is obtained; S9, Gradient deposition powder path switching: The dried Ti2AlNb powder is transported to the preheated substrate through the S6 coaxial four-way powder feeding method, and the Ti2AlNb layer is deposited according to the process parameters set by S7 and the laser path selected by S8. After a certain height is deposited, the powder path is directly switched to deposit the TiAl layer on the deposited Ti2AlNb layer to obtain an integrally formed dual alloy gradient material; S10, heat treatment process: The S9 integrally formed dual alloy gradient material is subjected to annealing heat treatment to obtain an integrally formed Ti2AlNb / TiAl gradient structure product; The laser path selected in S8 is a gradient single wall path or a gradient block path, where: The scanning path in the gradient single-pass wall path is a single-pass reciprocating cycle. The laser head moves from the origin to the positive direction of the Y axis. The laser scanning speed is 6-10mm / s. The laser emits light and delivers powder at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a speed of 1.5-2mm / s, and the lifting speed is ΔZ=0.5-0.7mm. No powder is emitted during the lifting. Then, the laser head moves along the negative direction of the Y axis, emitting light and delivering powder at the same time. When the set length is reached, the laser head is lifted upward along the Z axis at a speed of 1.5-2mm / s, and the lifting speed is ΔZ=0.5-0.7mm. No powder is emitted during the lifting. This is a cycle until the set number of layers is completed and printing is completed. In order to increase the heat input between passes and promote better fusion of gradient materials in the gradient block path, a short-side multi-pass overlap path is used to prepare block gradient materials, and the overlap rate between laser paths is 50%; the laser head moves from the origin to the positive direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and the powder is delivered at the same time. When the set length is reached, the laser head moves along the positive direction of the Y-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and the powder is delivered at the same time, and the overlap rate is 50%. When the set length is reached, the laser head moves along the negative direction of the X-axis, the laser scanning speed is 6-10mm / s, and the light is emitted and the powder is delivered at the same time. When the set length is reached, the laser head moves along the positive direction of the Y-axis, and the overlap rate is 50%, which is a cycle; after the Y-axis direction meets the length requirement, the laser head is lifted upward along the Z-axis, with a lift of ΔZ=0.7-1.0mm, and no powder is emitted during the lift. The lifting speed is 6-8mm / s, and the path of the previous layer is repeated until the cycle of the set number of layers is completed and printing is completed.
2. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: The Ti2AlNb alloy powder in S1 is spherical powder with a particle size of 45-150μm; the TiAl alloy powder is spherical powder, and its components include Ti-48Al-2Cr-2Nb and Ti-45Al-8Nb, and the powder particle size is 45-150μm; the drying treatment is carried out in a drying oven at 80-120℃ for 2-4h, and the water content of the dried Ti2AlNb alloy powder is not higher than 0.1%, and the water content of the TiAl alloy powder is not higher than 0.1%.
3. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: The pretreatment in S2 is to manually polish the substrate in the same direction with 80-120 mesh sandpaper before starting deposition, and then use a laser cleaning machine to remove the oil and oxide layer on the surface of the substrate. The roughness of the substrate surface is 200-50μm.
4. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: Specific process parameters for filling S4 with high-purity argon protective gas: the large environmental box purge time is 3-4h, the small environmental box purge time is 0.25-0.5h; the powder carrier gas flow rate is 0.8-1.5L / min, the powder delivery speed is 0.3-1r / min, the central protective gas flow rate is 15-45L / min, and the oxygen content in the environmental chamber is regulated to be lower than 20PPm, and the water content is lower than 0.01PPm.
5. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: The holding temperature of the preheating treatment in S5 is 300-500°C, and the holding time is 5-10min, which reduces the temperature difference in the molding chamber to within the range of 100-200°C.
6. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: In S6, the coaxial four-way powder feeding method is that the dried Ti2AlNb and TiAl alloy powders are fed into the molten pool from four directions at the same time during deposition, and the powder feeding carrier gas is argon.
7. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: Some process parameters of laser directed energy deposition in S7 include the number of cycle layers, laser power, scanning speed, lifting speed, powder feeding rate, and carrier gas flow rate. Other process parameters of laser directed energy deposition include lifting height and overlap rate.
8. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: The certain height in S9 is set according to the product with one-piece Ti2AlNb / TiAl gradient structure to be prepared. When the height of a single wall is set to 20mm, the single layer thickness is set to 0.5mm and the height is raised to 0.5mm. It takes 40 layers to reach the set height of 20mm. At this time, the powder path is switched to print the next material to realize the preparation of gradient materials.
9. The additive manufacturing method for integrally forming a Ti2AlNb / TiAl gradient structure according to claim 1, characterized in that: The heating rate of the annealing heat treatment in S10 is 10-20°C / min, the annealing temperature is 600-1000°C, the holding time is 2-6min, and then the furnace is cooled.
Citation Information
Patent Citations
Ti2AlNb particle plasticized TiAl-based composite material and preparation method thereof
CN112981156A
Electron beam selective melting additive manufacturing method and equipment for TiAl-Ti2AlNb gradient material
CN116079071A
Directional heat treatment method of Ti2AlNb alloy multistage gradient structure
CN117737619A
3D printing manufacturing method for titanium-aluminum dissimilar material
CN112517927A
Laser melting deposition connection method for dissimilar high-temperature alloy in aero-engine
CN113909478A